The Role of Islamic Religious Teachers Towards Effective Methods Memory Juz 30 in Class 6 Students Madrasah Ibtidaiyah Al Islamic - Nurfitriani, Sukma; Hasibuan, Akmal Riski Gunawan; Apriliantoni (Proceeding International Conference on Education, 2023)
Teachers play an important role in the success of learning. By choosing the right method, maximum results will be obtained. This study aims to determine the effectiveness of the method of memorizing Juz 30 in grade 6 students of Madrasah Ibtidaiyah Islami through the role of an Islamic religion teacher. Data collection techniques used are observation, interviews, and documentation. Data analysis was performed using a qualitative descriptive technique. The results of the study show that the role of the Islamic religion teacher is very important in increasing the effectiveness of the method of memorizing Juz 30 in grade 6 students. The teacher can choose the right method, such as the kinesthetic or drill method, to help students memorize the Al-Quran. The implication of this research is the importance of the role of Islamic religious teachers in increasing the effectiveness of the Al-Quran memorization method for grade 6 students. It is hoped that the teacher can choose the right and effective method in helping students memorize the Al-Quran so that students can more easily and quickly memorize the Al-Quran.